Antibiotic Sensitivity Pattern Of Different Isolated Bacteria In Pus Sample (Journal of Dhaka National Medical College & Hospital, 2019)
Background: Knowledge of local common pathogens and their resistance status can guide clinician to choose appropriate antibiotic for empirical treatment of patients.Objective: This study was undertaken to determine the frequently isolated organism from pus culture and to determine the antibiotic sensitivity patterns. The human skin and soft tissue infections (SSTIS) caused by microbial pathogens during or after trauma, burn injuries and surgical procedures. These result in the production of pus, a white yellow fluid comprised of dead WBC, cellular debris and necrotic tissues.Methods: Total 110 samples were collected from July 2018 to December 2018, to study antibiograms of various organism. All isolated bacteria were identified based on colony characteristics, Gram stain and standard biochemical tests and antibiotic susceptibility testing with disk diffusion method.Results: Most commonly encountered organism was Staphylococcus aureus (56.2%) followed by E. Coli (21.4%), Klebsiella (8.1%), Pseudomonas (6.4%), Streptococcus pyogens (5.6%) and Proteus (2.3%).Conclusion: The present study exemplify, there is an increasing need for gaining knowledge about the pattern of microbes and their antibiotic sensitivity and resistance, hence regular monitoring of bacterial sensitivity to antibiotics is essential.J. Dhaka National Med. Coll. Hos. 2019; 25 (01): 20-23